Sakuraya: strengthening cross-cultural understanding between Malaysia and Japan / Nurul Alyaa Ibrahim and Mohd Nadzri Mohd Najib - Ibrahim, Nurul Alyaa; Mohd Najib, Mohd Nadzri (Faculty of Pharmacy, 2025)
On 25th February 2025, the Faculty of Pharmacy UiTM Pulau Pinang Kampus Bertam successfully organised an event named “Sakuraya: Learning Language & Culture (Sakuraya: Mengenal Bahasa dan Budaya)”. This event, co-hosted with the Tun Abdul Razak Library (PTAR), aimed to strengthen the cultural and language acquisition between Malaysia and Japan.